FORMATION OF TEACHER'S IMAGE IN THE PROCESS OF STUDYING THE COURSE "FUNDAMENTALS OF STAGE AND SCREEN ART" - I.V. Razmolodchikova (Academy of Cognitive and Natural Sciences, 2010)
The author of the article stops on the problem of quality of professional preparation of teachers, shares with the experience of using of modern technologies at the process of teach ing of Russian Language Teaching Methodology.